Tinjauan Yuridis Pembaharuan RUU KUHP Dalam Tindak Pidana Lingkungan Hidup dan Sumber Daya Alam dikaitkan Dengan Undang-Undang Lintas Sektoral - Isti Puspitasari; Irwan Triadi (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
A number of studies related to the politics of criminal law in the Dfrat wetboek van straf recht (RKUHP) have increasingly tightened the state's grip on matters that de facto can be resolved by other types of law such as religion, decency and manners that already exist in society. At that point, efforts to think about the objectives of environmental and natural resource crimes in the RKUHP feel increasingly complicated to think about because this draft seems to be complicated and between various things, can consist of understandings, concepts, paradigms, which are related to and conflict with each other. another. This article uses normative legal research, the author obtains data from library materials which are usually called secondary data, which includes primary, secondary and tertiary legal materials. The author then studies and explores these legal materials and quotes theories or concepts from a number of literature, including books, journals, papers, newspapers or other written works related to the problem under study. This article explains that the position of the RKUHP regarding laws in the field of environment and natural resources is not yet clear, because the RKUHP does not expressly state its position regarding other laws. UU no. 10 of 2004 concerning the Preparation of Legislative Regulations also does not help provide answers because it does not recognize the general and specific designations or categories of laws as well as the requirements to fulfill these categories and this RKUHP is only able to absorb the criminal articles of each law. sectoral law, apart from other parts contained in the law. This means that the codification of this model consciously releases the historical and logical ties between the parts contained in each law.